Survey of Recently Board-Certified Prosthodontists on the Board Certification Process. Part 1: Demographics - Behnoush Rashedi, DMD, MS, MSEd,1 and Vicki C. Petropoulos, DMD, MS2 (Journal of Prosthodontics, 2003)
A survey of recently board-certified prosthodontists was conducted in 2001. The purpose of this survey was to identify trends that assisted candidates in attaining diplomate status.